PENGARUH SISTEM JUST IN TIME TERHADAP EFISISENSI BIAYA BAHAN BAKU - Gunadi, Arif; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of Just in Time method in the management of inventoryto the cost efficiency of raw materials at PT EKA BOGAINTI. The method of research is carried out by usingqualitative method, since this research is not intended to prove a hypothesis. Meanwhile the data analysistechnique is using descriptive analysis that is performed by comparing the data that has been obtained from theresearch and the existing theories. By implementating Just in Time purchase system the company will gainrelevant information related about the efficiency of raw materials cost and it is expected that it can eliminate allactivities that have no additional value by not storing raw material inventories in the warehouse. The value ofraw material inventories on PT EKA BOGAINTI from April to May 2014 can be known from theimplementation of Just In Time analysis that it is accordance with the traditional calculation result that is Rp1,957,155,329 while the result of Just In Time system is Rp 954,335,001 so there is an efficiency of rawmaterials cost from Just in Time policy is Rp 1,002,820,328.Keywords: Just in Time, Inventory, Raw Material Eficiency Cost.